2003
DOI: 10.1046/j.1440-0960.2003..x
|View full text |Cite
|
Sign up to set email alerts
|

Management of the primary cutaneous lymphomas

Abstract: Cutaneous lymphomas are rare and, although some are a manifestation of systemic lymphoma, the majority arise primarily from the skin. These primary cutaneous lymphomas comprise both T- and B-cell subtypes and represent a wide spectrum of disorders, which at times can be difficult to diagnose and classify. Classical therapeutic strategies include topical corticosteroids, phototherapy, radiotherapy, retinoids, extracorporeal photopheresis, topical chemotherapy, systemic chemotherapy and biological response modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 133 publications
0
19
0
Order By: Relevance
“…Effect on histone acetylation in mononuclear cells. Mononuclear cells were taken post-dose 1 at 3, 8,24, and 48 h, post-dose 2 at 48 h, and post-dose 3 at 72 h and whole-cell lysates were prepared in lysis buffer (Qiagen). Proteins (25 Ag) were separated by SDS-PAGE and Western blotting was done using anti-acetyl histone H3 and histone H4 antibodies (Upstate) and with anti -glyceraldehyde-3-phosphate dehydrogenase (Upstate) to control for protein loading.…”
Section: Methodsmentioning
confidence: 99%
“…Effect on histone acetylation in mononuclear cells. Mononuclear cells were taken post-dose 1 at 3, 8,24, and 48 h, post-dose 2 at 48 h, and post-dose 3 at 72 h and whole-cell lysates were prepared in lysis buffer (Qiagen). Proteins (25 Ag) were separated by SDS-PAGE and Western blotting was done using anti-acetyl histone H3 and histone H4 antibodies (Upstate) and with anti -glyceraldehyde-3-phosphate dehydrogenase (Upstate) to control for protein loading.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Furthermore, in 40% of patients with indolent CTCL, the disease can transform to a diffuse large cell phenotype carrying a particularly grave prognosis. 5,6 Therapy options for advanced-stage CTCL predominantly involve systemic approaches including immunomodulators such as interferon alpha, extracorporeal photopheresis (ECP), single or combination agent chemotherapy, oral retinoids, and immunotherapy such as alemtuzumab 6,7 or denileukin diftitox. 7,8 However, for patients with adverse prognostic factors, all of these approaches provide only limited-duration remissions, and the overall pattern is that of repeated relapse, and often death from complications of therapy or refractory disease.…”
mentioning
confidence: 99%
“…We found that patients with MF in tumor stage showed loss of CD3 and CD7, to those in patch and plaque stages and to patients with benign dermatoses. There are other reports on lower expression of CD7 [1,[24][25][26][27]. Most of authors state that deficiency of this antigen can represent a tool for diagnosis of MF [1,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…Treating of the disease includes topical corticosteroids, phototherapy, topical chemotherapy, radiotherapy, retinoids (in IA to IIB stages) and systemic chemotherapy. Modern therapy for cutaneous Tcell lymphoma is based on the cellular and molecular pathways involved in the pathogenesis of CTCLs includes monoclonal antibodies and biological response modifiers (in IIB to IV stages) [1]. Recently it was reported that the use of allogenic stem cell transplantation can cause long-term durable remissions of more than 3 years in case of patients with CTCL [2].…”
mentioning
confidence: 99%